Edukasi Cuci Tangan Pakai Sabun Sebagai Upaya Peningkatan Kualitas Kesehatan di Lingkungan SD Negeri Ai Limung - Ana Lestari; Luh Putu Sri Yuliastuti; Iga Maliga; Rafiah Rafiah; Asri Reni Handayani; Herni Hasifah; Nur Arifatus Sholihah (Jurnal Nusantara Berbakti, 2024)
School-aged children have a habit of paying less attention to hand washing behavior, especially in the school environment. Although simple and effective, promoting hand washing for disease prevention is still a challenge. The habit of washing hands with soap is still a global concern because people still forget the habit of washing their hands. The focus of the activity is school-aged children who will become "Agents of Change" in the future. This activity was attended by students aged 7-12 years who attended Ai Limung State Elementary School and totaled 54 children. After following this counseling, it is hoped that students will always be able to maintain cleanliness, especially hand hygiene by diligently washing their hands with soap to prevent them from infectious diseases. The level of knowledge of the students after this counseling increased, this can be seen from their fluency in practicing how to wash their hands with soap and answering the questions given properly and correctly. It is hoped that this activity can increase knowledge and increase awareness of Ai Limung State Elementary School students about how important it is to wash your hands with soap to always maintain cleanliness to avoid germs